Palynological analysis of Lama guanicoe modern feces and its importance for the study of coprolites from Patagonia, Argentina - Velázquez, Nadia Jimena (2012)
The aim of the present study was to develop a seasonality palynological model from modern feces of Lama guanicoe for the interpretation of pollen found in coprolites. For this purpose, fecal samples of L. guanicoe were collected during a year from dung piles located in the ecotone Subantarctic Forest-Patagonian Steppe, Perito Moreno National Park (PMNP) (NW Santa Cruz province, Argentina). For every season, the food items were characterized and the post-depositional pollen contamination of feces was evaluated. The results showed differences among the pollen sets of feces from every season and no post-depositional pollen contamination of the superficial fecal subsamples. Pollen concentration and percentage values evidenced high pollen abundance of: a) Asteraceae subfam. Asteroideae-Senecio type, Mulinum spinosum and Rumex in summer feces; b) Poaceae in autumn feces; c) Empetrum rubrum in winter feces; and d) Nassauvia, Plantago and Poaceae in spring feces. Seasonality variations in the feces were related to the phenology of plants, to variations in the diet and to the supply of palatable resources for L. guanicoe. This seasonal feces model will be useful as an analog in studies on Holocene camelid coprolites found in Cerro Casa de Piedra (PMNP) sites. It will allow clarifying the seasonality in site use. On the other hand, it will contribute data to the L. guanicoe´s diet, which represent an important information for the species´ regional sustainable management.